2013
DOI: 10.1200/jco.2013.49.2173
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Double-Blind, Placebo-Controlled, Phase III Chemoprevention Trial of Selenium Supplementation in Patients With Resected Stage I Non–Small-Cell Lung Cancer: ECOG 5597

Abstract: A B S T R A C T PurposeSelenium has been reported to have chemopreventive benefits in lung cancer. We conducted a double-blind, placebo-controlled trial to evaluate the incidence of second primary tumors (SPTs) in patients with resected non-small-cell lung cancer (NSCLC) receiving selenium supplementation. Patients and MethodsPatients with completely resected stage I NSCLC were randomly assigned to take selenized yeast 200 g versus placebo daily for 48 months. Participation was 6 to 36 months postoperatively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 32 publications
2
73
0
2
Order By: Relevance
“…Several prominent clinical trials however employing dietary antioxidants yielded disappointing anticancer results 42, 43, 44. Thus, current consensus is that rather than attempting to neutralize ROS, treatment strategies aimed at reducing ROS production might represent an effective alternative approach 45.…”
Section: Discussionmentioning
confidence: 99%
“…Several prominent clinical trials however employing dietary antioxidants yielded disappointing anticancer results 42, 43, 44. Thus, current consensus is that rather than attempting to neutralize ROS, treatment strategies aimed at reducing ROS production might represent an effective alternative approach 45.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the statistical results showed that high-dosage Vitamin E supplement (> or =400 IU/d) increased mortality and should be avoided [65]. On the other hand, Se is believed to be safe to use but showed no benefit to non-smallcell lung cancer [51]. Other clinical trials also indicated that Vitamin E intake increased the risk of prostate cancer, and Se supplementation intake could increase the prostate cancer risk in men with preexisting high levels of Se [50].…”
Section: No Significant Advantage Of Antioxidants Observed In Clinicamentioning
confidence: 94%
“…Early chemoprevention trials focused on vitamin A and beta carotene failed to show a protective effect, and some trials suggested a potential increase in lung cancer risk (11)(12)(13). Furthermore, a recent phase III trial failed to demonstrate efficacy for selenium supplementation (14). There are, however, a number of agents, including iloprost (15), myoinositol (16), and cyclooxygenase-2 inhibitors, that are currently being explored in early-phase trials.…”
Section: Epidemiology and Preventionmentioning
confidence: 99%